Exploring the Mediating Role of Innovative Capability between Entrepreneurial Leadership and MSME Performance - Rony Nur Triwibowo; Asharryadi Noegroho; Sudadi Pranata Pranata (International Journal Business and Entrepreneurship, 2025)
This study sought to ascertain the impact of entrepreneurial leadership on the performance of food and beverage MSMEs in Cilacap. The research sample comprised 130 MSME participants. The sample was obtained using an online survey. This study employed Smart PLS 3.0 for analysis. The study indicates that entrepreneurial leadership positively influences MSME performance and innovative capability. Innovative capability favourably influences MSME performance and mediates the relationship between entrepreneurial leadership and MSME success. This study's drawback lies in its focus on food and beverage MSMEs in Cilacap, hindering the generalizability of the findings to other sectors or locations with distinct features. This study enhances the literature by empirically confirming the mediating function of Innovative Capability between Entrepreneurial Leadership and the performance of MSMEs, specifically within Indonesia's food and beverage industry. These findings emphasize the necessity for MSME leaders to cultivate entrepreneurial attributes and promote an atmosphere conducive to innovation. Organizations can enhance their performance metrics by investing in the Innovative Capabilities dimension, which encompasses a strategy emphasis on innovation, a conducive company culture, and practical knowledge management. Policymakers and practitioners can utilize these insights to build training programs and policies that foster leadership development and innovation in MSMEs. Additional research is advised to investigate other mediating or moderating variables, like technological advancements, market situations, or organizational frameworks.